Cochlear implantation surgery experience of a tertiary clinic - Mutlu, Ahmet; Iseri, Mete; Durgut, Merve; Topdag, Murat; Erdogan, Selvet; Ozturk, Murat (DERMAN MEDICAL PUBL, 2018)
Aim: Cochlear implantation (CI) is a commonly performed procedure for severe to profound deafness in patients. It has been widely used for this purpose, and it becomes more complicated than expected for new institutes. In this report, we aimed to discuss the patient features, surgery indications, results of the CI surgeries in the experience of a single center. Material and Method: We retrospectively analyzed 65 patients who were underwent CI in a tertiary hospital. Hearing loss etiologies, hearing results and postoperative complications were assessed. Results: Sixty-five patients were evaluated within in two groups as 0-6 years-old and over 7 years-old. Twenty-nine patients were placed in 0-6 years-old group, and 36 patients were placed in over 7-years-old group. In 0-6-years-old group

27 patients hearing loss remained idiopathic, but 1 patient had Cogan syndrome, and 1 patient had a cochlear malformation. Hearing gain of the entire group was found statistically significant (p<0.000). In over 7-years-old group

1 patient underwent CI for each of indications: traumatic hearing loss, iatrogenic cochlear damage, Meniere's disease, chronic otitis media, electrode renewing. The etiology of the 31 patients were not revealed in the over 7-years-old group. The hearing gain of the group was found statistically significant (p<0.000). One patient had a dural injury, and 1 patient had a round window gusher. Six patients had postoperative vertigo. Post-implantation facial nerve stimulation was revealed in 1 patient. Discussion: CI is a very revolutionary technic for the hearing-impaired patients. The implant success is strongly related to the patient management and appropriate surgical technics.
Keywords: Cochlear Implantation; Hearing Loss; Complication; Indication